Identifying the house buyer needs and product concepts for the mass development of green home in Malaysia. - Ismail, Radzi; Mohd Shafiei, Mohd Wira; Said, Ilias (2008)
Green building is defined as a whole systems approach to the design, construction and operation of buildings – from the early stages of development through the final finishes in the home. The concept of green home is the convergence of three fundamental objectives, namely, the conservation of natural resources, the improvement in energy efficiency, and better indoor air quality. For green buildings to be more comfortable and satisfying than conventional buildings there must be some features that are unique, or at least more common, to their design that could contribute to a better indoor environmental quality. In Malaysia, there had been little effort to mass-develop green homes so that these houses can be bought easily by the house buyers. Because of this scenario, a marketing research focusing on reducing the uncertainty associated with any new product such as these green homes, need to be carried out before any property developer will want to build these houses, and consequently, for these houses to be accepted by the house buyers. To ensure continued growth in the adoption of green building technologies, it is important to ensure that customer needs are being addressed. Despite the good examples shown by the other developed countries on how to build houses sustainably, Malaysia are relatively behind so far in this aspect. This, despite the fact that, the technology to build sustainable house are there for the Malaysian developers and construction professionals to harness. This paper attempts to put into effect a marketing research that looks into the possibility of mass-developing green homes in Malaysia. We will only look into the house buyers’ green homes needs, and then, the right concepts for the homes. Hence, both sides in the market will be studied: the providers (consist of property developers, contractors, and construction consultants) and the house buyers.